Assessment of Functional Rhinoplasty with Spreader Grafting Using Acoustic Rhinomanometry and Validated Outcome Measurements - Marek A. Paul, MD; Parisa Kamali, MD; Austin D. Chen; Ahmed M. S. Ibrahim, MD, PhD; Winona Wu, BA; Babette E. Becherer, BA; Caroline Medin, BS; Samuel J. Lin, MD, MBA (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. Rhinoplasty is 1 of the most common aesthetic and reconstructive plastic surgical procedures performed within the United States. Yet, data on functional reconstructive open and closed rhinoplasty procedures with or without spreader graft placement are not definitive as only a few studies have examined both validated measurable objective and subjective outcomes of spreader grafting during rhinoplasty. The aim of this study was to utilize previously validated measures to assess objective, functional outcomes in patients who underwent open and closed rhinoplasty with spreader grafting. Methods:. We performed a retrospective review of consecutive rhinoplasty patients. Patients with internal nasal valve insufficiency who underwent an open and closed approach rhinoplasty between 2007 and 2016 were studied. The Cottle test and Nasal Obstruction Symptom Evaluation survey was used to assess nasal obstruction. Patient-reported symptoms were recorded. Acoustic rhinometry was performed pre- and postoperatively. Average minimal cross-sectional area of the nose was measured. Results:. One hundred seventy-eight patients were reviewed over a period of 8 years. Thirty-eight patients were included in this study. Of those, 30 patients underwent closed rhinoplasty and 8 open rhinoplasty. Mean age was 36.9 ± 18.4 years. The average cross-sectional area in closed and open rhinoplasty patients increased significantly (P = 0.019). There was a functional improvement in all presented cases using the Nasal Obstruction Symptom Evaluation scale evaluation. Conclusions:. Closed rhinoplasty with spreader grafting may play a significant role in the treatment of nasal valve collapse. A closed approach rhinoplasty including spreader grafting is a viable option in select cases with objective and validated functional improvement.